MENCEGAH SENGKETA TANAH - Abdul Hamid Usman (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2022)
Land disputes occur because they are related to the control of land rights. The control of land rights is carried out in accordance with the provisions of the legislation, so land disputes can be avoided, can be prevented. Minimization of conflict and optimization of order can be stated as the ultimate goal of using law as a regulator of people's lives. Due to the importance of this problem, on September 24, 1960, Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles was enacted, which is usually called the Basic Agrarian Law and abbreviated as UUPA. The UUPA is the embodiment of Article 33 paragraph (3) of the 1945 Constitution. The land issue is part of the agrarian problem. In connection with this, the approach in this paper is carried out in a normative juridical manner, namely the type of research that uses secondary data or library data as the main data. Based on the discussion carried out, it can be concluded that preventing land disputes can be done by: (1) administering land rights certificates. If the land is still in the form of land rights according to customary law or civil (western) law, then convert the rights and register the land, until a certificate of land rights is issued; (2) keep the land certificate carefully; (3) create clear and permanent land boundaries; (4) construct buildings and plant perennials; (5) make a nameplate of the owner on the land in question as a notification to the community; (6) the transfer of land rights must always be before the Land Deed Making Official (PPAT)/Notary.